Musical fit and willingness to pay for utilitarian products among university students. - Sze, Yeoh Pei Joanne (Universiti Putra Malaysia Press, 2010)
This study investigated the impact of musical fit on consumers? Purchase intentions regarding utilitarian products. Participants were shown pictures of products and asked to state the maximum they would be willing to pay for each item. Following that, participants were also shown pictures of two competing utilitarian products, one being a more 'upmarket' (e.g. Duracell batteries) version than the other (e.g. Eveready batteries), and they were asked to choose one of the two while being exposed to either Malay music, pop music, classical music or no music condition. Participants were not influenced to pay more for utilitarian products when being exposed to the different musical styles (and no music) condition. Participants also did not necessarily choose the more "upmarket" product when exposed to different musical styles (and no music) condition. This suggests that musical fit may not influence purchase intentions for utilitarian products.